Pengaruh Ekstrak Batang Bajakah Tampala (Spatholobus littoralis Hassk) Terhadap Perilaku Mencit Jantan (Mus musculus) yang Terinfeksi Bakteri Salmonella typhimurium - Bela Novita Amaris Susanto; Nofri Zayani; Nindita Clourisa Amaris Susanto (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Bajakah tampala stem (Spatholobus Littoralis Hassk) has the potential to be used for health, especially to increase immunity. The results of the phytochemical screening test showed that the main ingredients of bajakah were saponins, flavonoids, and tannins. The study used an experimental design with a completely randomized design (CRD), which consisted of 5 treatments (dose) and 6 replications. The dose is aquadest (K1/control); 25 mg/kg (K2); 50 mg/kg (K3); 100 mg/kg bw (K4) and 30 mg/kg of brand X immunomodulatory drug (K2). Mice were injected orally with the treatment according to the prescribed dose for 30 days. On the 31st day, the mice were infected with Salmonella typhimurium bacteria. On the 32nd-34th day, physical condition and activity were observed. data on changes in physical condition and activity were processed by descriptive statistics. Batang bajakah tampala extract (Spatholobus littoralis Hask) can improve the immune system as seen from the behavior and external morphology of mice (Mus Musculus) exposed to salmonella typhimurium, especially at a dose of K4 (100 mg/kg bw). Keywords: Bajakah tampala, behavior, mice, salmonella typhimurium